Evaluation of obesity as an independent risk factor for medically attended laboratory‐confirmed influenza - Coleman, Laura A. (Influenza Other Respir Viruses, 2012)
Please cite this paper as: Coleman et al. (2013) Evaluation of obesity as an independent risk factor for medically attended laboratory‐confirmed influenza. Influenza and Other Respiratory Viruses 7(2) 160–167. Background  The relationship between obesity and susceptibility to influenza infection in humans is unclear. Morbidly obese people were at an increased risk of complications from 2009 pandemic H1N1 influenza [A(H1N1)pdm09]. Objective  The goal of this study was to determine whether medically attended, laboratory‐confirmed influenza is independently associated with obesity in adults with acute respiratory illness. Patients/Methods  Adults ≥20 years with a medical encounter for acute respiratory illness were recruited from a population cohort during the 2007–2008 (n = 903), 2008–2009 (n = 869), and 2009 pandemic (n = 851) season. Nasopharyngeal swabs were tested for influenza by real‐time reverse‐transcription polymerase chain reaction. Body mass index (BMI) was calculated using data from the electronic medical record. Logistic regression evaluated the association between influenza and obesity, adjusting for gender, vaccination, age, and high‐risk medical condition. Results  Influenza was detected in 50% of patients in 2007–2008, 15% in 2008–2009, and 14% during the 2009 pandemic. Predominant seasonal viruses in this population were A/H3N2 in 2007–2008, and A/H1N1 and B in 2008–2009. Mean (±SD) BMI was 30·58 (±7·31) in patients with influenza and 30·93 (±7·55) in test‐negative controls during all seasons. Mean BMI of patients with influenza did not vary by season. After adjusting for confounders, neither obesity nor extreme obesity were associated with influenza by season or for all years combined (OR 0·95: 95% CI 0·75, 1·20 and 1·10: 0·80, 1·52, respectively, for obesity and extreme obesity, all years). Conclusions  Obesity was not associated with medically attended influenza among adults with acute respiratory illness in this population.